The Strategy Of The Homeless Survival In Surakarta - Retno Woro Kaeksi; Umrotun Umrotun; Susanto Susanto; Triana Nur Handayani; Satriyo Nugroho (Forum Geografi, 2004)
The research is carried out in Surakarta. The goal of the study is to know: the characteristic of the homeless, the factors that cause them to he the homeless and the strategis of the homeless to survive in Surakarta. The research uses survey method, while its area is chosen purposively. The research also uses primary and secondary data. The primary data is obtained by interviewing the respondents with questionnaire, while secondary data is based on the information got from the relevant institution.